Inclusion of broken rice in meat-quail diets at different ages - Silva, Wilson Araújo da; Pereira , Adriana Aparecida; Lima Júnior, Dorgival Morais de; Lima, Carolyny Batista; Santos, Graziela da Silva; Almeida, José Rafael Silva de; Silva , Érika Bruna de Araújo; Barros Júnior, Romilton Ferreira de (Acta Scientiarum. Animal Sciences, 2020)
The aim of this study was to evaluate the inclusion of 50% broken rice (BR) in diets for meat quail from 1 to 35 days old, starting at different ages. A total of 875 mixed quail were allocated to five treatments in a completely randomized design with five replicates of 35 birds. The treatments consisted of a maize- and soybean meal-based control diet and four other similar diets in which the inclusion of 50% BR was started at different ages, namely, 1st, 8th, 15th and 22nd days. Feed intake, weight gain, feed conversion and mortality rate were evaluated weekly. At 35 days, 10 quail per plot were weighed and selected to be slaughtered for evaluations of live weight, carcass yield and gizzard yield. Lastly, a study of economic viability was carried out. No significant difference (p > 0.05) was detected for the performance parameters, live weight or carcass yield, but a higher gizzard yield was found (p < 0.05) in the treatment without BR. The inclusion of BR from the first day of life provided better economic viability. Diets with a maximum inclusion of 50% BR can be formulated for meat quail at any age.